Subgroup analysis of Brazilian participants of a medical leadership competencies instrument: a cross-sectional survey study of the Latin American Cooperative Oncology Group (LACOG) and the Academy of Leadership Sciences Switzerland (ALSS) - Max Senna Mano; Rafaela Gomes Jesus; Carlos Henrique Escosteguy Barrios; Wanessa Cassemiro Fernandes; Leandro Jonata de Carvalho Oliveira; Abna Faustina Sousa Vieira; Renan Orsati Clara; Antônio Luiz Frasson; Gustavo Nader Marta; Sérgio Daniel Simon; Cynthia Villarreal-Garza; Gustavo Werutsky; et al. (Brazilian Journal of Oncology, 2022)
Introduction: We previously published the results of a medical leadership (ML) competencies instrument applied to Latin-American (LA) physicians with a leadership position, which disclosed meaningful differences in the valuation of specific ML competencies by LA physicians as compared to a similar survey applied to healthcare professionals from North America and Europe (NA/EU). Because the most pronounced differences in the responses were in terms of country of medical practice, we felt that an analysis focused on the Brazilian participants (a culturally more homogeneous population) could provide further insights into understanding other subgroup differences. Objectives: We aimed to: 1) compare the responses from the Brazilian participants with those of the NA/EU survey and 2) perform subgroup analyses within the Brazilian participants. Design and Setting: Cross-sectional survey study applied only once. Material and Methods: Between November 13th and December 12th, 2018, we collected 217 responses. Results: There were (n=135/63%) Brazilian participants. The valuation of a set of ML competencies by Brazilian physician-leaders roughly match those of the main study (task management remaining the most valued set of competencies versus 3rd in the NA/EU survey). However, significant differences in the responses were seen in some subgroups, especially in terms of the impact of seniority (which no longer appears to affect the responses) and gender (with women no longer placing a higher value on innovation competencies). Conclusion: This analysis reinforces the existence of significant cultural differences within the LA participants, and that these cultural variations can significantly affect the valuation of specific ML competencies.